Public executions: the death penalty and the media - Kudlac, Christopher (Crime, media, and popular culture, 2007)
Introduction -- Capital punishment, the media, and changing sensibilities -- A short history of the death penalty -- Serial killers, 1977-1994 -- Protest cases, 1994-2002 -- Federal death penalty and terrorism -- A focus on the system : moratorium, DNA cases, and the Supreme Court -- Conclusion